Reading Voices by Sulaiman Fayyad: At the Intersection of Feminist and Postcolonial Critique (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
With feminist and postcolonial critical thought as its point of departure, this paper undertakes a reading of Sulaiman Fayyad’s use of multiperspectivity in narration as an intentional break with one-sided narrative occurring from a hegemonic position. The objective of this analysis is to draw attention to the layered, comprehensive story that Fayyad chooses to tell using the voices of both male and female protagonists: a story about colonialism, violence, traditions, patriarchy and the instrumentalization of women for the preservation of the colonial/patriarchal social order and its power dynamic.The plot of the novel, set in the period immediately after decolonization, points to the unresolved issue of women’s freedom and rights. Applying the aforementioned critical approaches, while engaging with the feminist thought of Nawal El Saadawi and psychoanalytical insights of colonialism by Frantz Fanon, provides a more nuanced interpretation of the story. Repetitive generalizations about the ‘Islamic East’ or ‘Arab women’ as a monolith, and the resulting prejudice, made their way into the Western ‘common sense’, often ascribing the challenges faced by women in a variety of societal, political, and historical contexts to Islam as a specifically misogynist religion. According to Nawal El Saadawi, the exaggerated focus on some aspects or manifestations of inequality increases the suppression of real life social and economic issues and contributes to the erasure of everyday emancipatory struggle. A liberated society is founded upon awareness of the conditions of general subjugation, with a need to reveal the specific forms of violence that women are subjected to. Sulaiman Fayyad’s novel Voices sheds light on the concealed violence, internalized and externalized, affecting the people captured in superficially apparent resolution of colonial subjugation. Through acknowledgement of the anticolonial thesis at the basis of the novel that includes the critique of patriarchy as a ‘natural’ traditional state of being of a society, the interpretive process in this paper points to the avoidance of stereotypical oversimplifications and essentialisms in Fayyad’s work, as well as its contribution to the feminist cause.By emphasizing the anticolonial and the feminist dimension of the novel, the paper illustrates how the patriarchal order, as depicted in the remote rural community in the story, remains the last stronghold of colonial relations, where the colonization of women’s bodies continues, leaving behind trauma that results in the further reproduction of violence. The novel Voices tells the story of the consequences of the arrested development of the liberation process, where in place of completed decolonization, patriarchy continues to act as an outlet for coloniality and a channel for the continuation of violent power orders.
Keywords: colonialism; patriarchy; decolonization; Third world feminism; Egypt